Prediction of the course of acute odontogenic pathology with pronounced osteomyelitis by immunoglobulin and cytokin evaluation - A. I. Yaremenko; O. V. Galkina; A. R. Moshir Falsafy; A. V. Yakovleva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The aim of our trial was detection of the most significant clinico-laboratory factors in the saliva and blood samples of the patients with odontogenic osteomyelitis in order to predict severity of the clinical course of osteomyelitis and to choose the optimal treatment tactics.